Use of Non-pharmacological Therapies in Individuals With Migraine Eligible for Treatment With Monoclonal Antibodies Targeting Calcitonin Gene-Related Peptide (CGRP)-Signaling: A Single-Center Cross-Sectional Observational Study - Rundblad, Lucas; Cullum, Christopher Kjaer; Sacco, Simona; Gil-Gouveia, Raquel; Uludüz, Derya; Do, Thien Phu; Amin, Faisal Mohammad (Frontiers in Pain Research, 2022)
Introduction Accessibility of treatment with monoclonal antibodies targeting the calcitonin gene-related peptide (CGRP) signaling pathway is impeded by regulatory restrictions. Affected individuals may seek out other services including non-pharmacological therapies. Thus, we found it timely to ascertain the use of non-pharmacological therapies in individuals with treatment-resistant migraine eligible for and naïve to treatment with CGRP-signaling targeting monoclonal antibodies. Methods We conducted a single-center cross-sectional observational study of patients eligible for and naïve to treatment with monoclonal antibodies targeting CGRP or its receptor. We recorded demographical information (gender, age, educational level, employment status, and income), disease burden (frequency of headache days and migraine days), previous use of preventive pharmacological medications for migraine, and use of non-pharmacological therapies over the past 3 months including frequency of interventions, costs, and patient-reported assessment of efficacy on a 6-point scale (0: no efficacy, 5: best possible efficacy). Results We included 122 patients between 17 June 2019 and 6 January 2020; 101 (83%) were women and the mean age was 45.2 ± 13.3 years. One-third (n = 41 [34%]) had used non-pharmacological therapy within the past 3 months. Among these participants, the median frequency of different interventions was 1 (IQR: 1–2), the median number of monthly visits was 2.3 (IQR: 1.3–4), mean and median monthly costs were 1,086 ± 1471, and 600 (IQR: 0–1200) DKK (1 EUR = 7.5 DKK), respectively, and median patient-reported assessment of the efficacy of interventions was 2 (IQR: 0–3). Conclusion Even in a high-income country with freely accessible headache services and universal healthcare coverage, there was a non-negligible direct cost in parallel with low satisfaction for non-pharmacological therapies among patients at a tertiary headache center.